Nurcholish Madjid's Ideas on Renewal of Islamic Education in Indonesia - Lidyaningsih, Windy; Hanif, Muh. (Universitas Islam Indonesia, 2023)
This study aims to examine Nurcholish Madjid's thoughts on the reforms of Islamic education in Indonesia. This paper uses library research method by collecting sources from documents related to the theme of Islamic education reform. The sources are triangulated to determine their credibility and authenticity and then analyzed using content analysis. The results of the research found that Nurcholish Madjid proposed several important renewal ideas that can be applied to Islamic education in Indonesia, including modernization and secularization. Modernization in Islamic education can be applied in terms of the materials delivered and the education system while secularization in Islamic education can be promoted to give the right to think freely for every learner as a human being who has freedom of thought.